Emergence of Cyber Crime and Prevention Strategies in Indian Scenario - Chauhan , Raksha (Gyan Management Journal, 2014)
The number of cyber crimes in India has raised over the year and especially financial sectors are facing this problem widely. The major cyber crimes reported, in India, are denial of services, defacement of websites, SPAM, computer virus and worms, pornography, cyber squatting, cyber stalking and phishing. The failure towards providing trusted secure services in modern computer network technologies has a remarkable socio-economic impact on global enterprises as well as individuals. The growing danger from crimes committed against electronic information on computers, is alerting us to claim attention in national capitals. Dedicated legislation on cyber crime that can supplement the Indian Penal Code is demand of the state of art In this paper an attempt has been made towards cyber crime emergence and prevention strategies in Indian scenario. We are also throwing light on present status of cyber crime in India, steps taken by Indian government to avoid cyber crime and also upon international accordance and solutions to deal with the same.
Keywords: Cyber Attacks; Cyber Crimes; Cyber law; I. T. Act 2000; Information Technology and National Security